A Systematic Review and Meta-Analysis on a Disease in TCM: Astragalus Injection for Gathering Qi Depression. (12th February 2020) - Ha, Yanxiang; Huang, Po; Yan, Yumeng; Xu, Xiaolong; Li, Bo; Guo, Yuhong; Liu, Qingquan
Abstract : Zong Qi depression is a disease recorded in the literature of Chinese traditional medicine for a long time. In recent years, the theory of Zong Qi depression has been more and more applied to the diagnosis and treatment of a variety of diseases. Astragalus is the most important drug used to treat the depression of Zong Qi. Meanwhile, Astragalus injection is also widely used in a variety of diseases in accordance with the manifestations of Zong Qi subsidence. However, there is a lack of systematic review or meta-analysis of the clinical effect of Astragalus injection in the treatment of Zong Qi subsidence. Therefore, we searched for diseases characterized by symptoms of Zong Qi subsidence (including heart failure, respiratory failure, acute respiratory distress syndrome, and acute lung injury) and evaluated the effect of Astragalus injection in these diseases with mortality and distance of a 6-minute walking test. The results showed that the mortality of patients with subsidence of Zong Qi decreased in 1 month (OR, 0.26 [0.12, 0.61], 95% CI, P = 0.002 ) and 1 year (OR, 0.38 [0.20, 0.69], 95% CI, P = 0.002 ) after using Astragalus injection. The distance of 6-minute walking test after 7 (MD, 91.60 [6.89, 176.31], 95% CI, P = 0.03 ), 14 (MD, 22.62 [13.80, 31.43], 95% CI, P < 0.00001 ), and 28 days (MD, 108.31 [30.02, 186.59], 95% CI, P = 0.007 ) of using Astragalus injection also increased. Therefore, we believe that Astragalus injection has a certain therapeutic effect on the depression of Zong Qi.